A magyarországi K+F helyzete, európai uniós tükörben - Balogh, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
The situation and efficiency of R & D activities in Hungary were analysed with the use of Eurostat and Central Statistical Office data. The conclusion was drawn that the system of indexes used and published officially is hardly suitable for presenting the existing problems and for carrying out strategic analyses. The analysis of the official data leads to the conclusion that it would be advisable to use long statistical time series and to apply indexes showing specific development more extensively. The situation of R & D in Hungary is presented in the paper from this approach. We have found that certain problems hindering R & D in Hungary, such as the insufficient concentration of researches, the insufficient proportion of business-like researches and researches promising direct economic benefits in general, the problems of the distribution of research investments between fields of science etc., could not be solved in the period after the change of the regime, either. In many respects the current situation of R & D is definitely worse than before the change of the regime, first of all as concerns the financing of R & D. The dominance of publication-centeredness as one of the approaches indicating efficiency may overshadow the fundamental duality in the relationship of R & D with economy, namely that economy should be not only the source but also the primary beneficiary of R & D activities.